PALM SUGAR BUSINESS DEVELOPMENT IN MELATI VILLAGE, PERBAUNGAN DISTRICT, SERDANG BEDAGAI REGENCY - Sofia Rahmi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
This program of community service activities aims to provide education to the public about processing palm sugar into ant sugar. With the assistance in the form of ant sugar processing equipment and education about palm sugar processing so it is not easy to taste acid can increase the knowledge of entrepreneurs in developing their businesses. Palm sugar which was originally a sugar that easily melts and is packaged in a very simple form will have a higher selling value because it is made in the form of ant sugar and packaged in such a way. The tim of this community service activity give educate in the form of the equipment. And its processing so that they are able to understand more the process of palm sugar into ant sugar.